Gall-bladder sensitivity to cholecystokinin in patients with gall stones. Issue 6208 (19th January 1980) - Northfield, T C; Kupfer, R M; Maudgal, D P; Zentler-Munro, P L; Meller, S T; Garvie, N W; McCready, R
Abstract : Gall-bladder sensitivity to cholecystokinin (CCK) was determined by dynamic cholescintigraphy in 18 patients with radiolucent gall stones and 18 matched controls during an infusion of CCK in which the rate of infusion was increased. In 10 of the matched pairs the patient was more sensitive than the control, in one the control was more sensitive, and in seven no difference was detected (p = 0.012). It is concluded that patients with cholesterol gall stones have increased gall-bladder sensitivity to CCK, and that this may be important in the pathogenesis of this disease.